Angewandte Literaturwissenschaft – Überlegungen zu Perspektiven einer Germanistik der Zukunft - Wolting, Stephan (Glottodidactica, 2011)
Recently there is a big discussion about the sense and nonsense of what we called the former philology, especially in the field of German studies. The author tries to focus his consideration of German literature on the importance of studying German literature in future and what this subject can get a special use for certain sustainability and facilities. He points out some ways in which we can deal with that in future as students, but as teachers too.